Coronary heart disease epidemiology from aetiology to public health - Marmot, M. G.; Elliott, P. (Paul) (Oxford : Oxford University Press, 2005)
This second edition provides authoritative and readable insight into the wide field of coronary heart disease epidemiology. It reviews major risk factors from various perpectives and is an important textbook on the epidemiology and prevention of heart attacks.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Coronary heart disease -- Epidemiology